História natural e mecanismos utilizados na navegação no opilião Heteromitobates discolor (Arachnida,Opiliones) - Silva, Norton Felipe dos Santos [UNIFESP] (2015)
Animals may use external or internal cues to navigate towards an original location. Here we studied the homing ability of the harvestman Heteromitobates discolor (Arachnida, Opiliones). We tested the importance of (1) their own movement (proprioceptive cues), (2) olfaction (own clutch and own odor surrounding the clutch) and (3) vision. We used egg-guarding females motivated to return to their clutches after being manually dislodged to a distance of 1m from the eggs. We predicted that homing would be negatively affected in the absence of one or more of these cues, the success being measured by the return of females to the clutches. We hampered proprioception by not allowing females to walk, removed vision by painting the eyes and removed the odors by removing the clutch and cleaning its surroundings. We conducted all the experiments in the field. Using adequate controls, we compared the return success of females under distinct treatments. Proprioception increases 3x the chances of a successful return. In the absence of proprioception, vision increases 7x the return success. The odor of the clutches and their surroundings did not affect the return success. We conclude that proprioceptive and visual cues are important for homing in the harvestman H. discolor.